Determinants of viral load suppression among orphaned and vulnerable children living with HIV on ART in Tanzania - Ally, Amal; Exavery, Amon; Charles, John; Kikoyo, Levina; Mseya, Remmy; Barankena, Asheri; Fovo, Rose; Temu, Akwila (Frontiers in Public Health, 2023)
Introduction In Tanzania, only 66% children 0–14 years living with HIV know their HIV status, 66% are on treatment while 47% of children on ART are virally suppressed. Although retention on ART and poor adherence remain a challenge for children living with HIV, orphans and vulnerable children (OVC) face a greater limitation of access to and utilization of comprehensive HIV care and treatment. In response to this, the current study assessed the determinants of viral load suppression (VLS) among OVC aged 0–14 years living with HIV enrolled in HIV interventions. Methods This was a cross-sectional study that used secondary data collected by the USAID Kizazi Kipya project in 81 district councils of Tanzania. Included in this study are 1,980 orphans and vulnerable children living with HIV (OVCLHIV) (0–14 years) enrolled and served by the project for 24 months. Data analysis involved multivariable logistic regression, with viral load suppression as the outcome of interest and HIV interventions as the main independent variables. Results The overall VLS rate among the OVCLHIV was 85.3%. This rate increased from 85.3, 89.9, 97.6 to 98.8% after 6, 12, 18, and 24 months of retention on ART, respectively. Similar rates were observed as the duration of adherence to ART increased. In the multivariable analysis, OVCLHIV attending people living with HIV (PLHIV) support groups were 411 times more likely to be virally suppressed than those not attending (aOR = 411.25, 95% CI 168.2–1,005.4). OVCLHIV with health insurance were 6 times more likely to achieve viral suppression than those without (aOR = 6.05, 95% CI 3.28–11.15). OVCLHIV with >95% adherence to ART were 149 times more likely to be virally suppressed than those not adherent to ART (aOR = 148.96, 95% CI 42.6–520.6, p < 0.001). Other significant factors included food security and family size. OVCLHIV reached by the different HIV community-based interventions were more likely to be virally suppressed than those who were not. Discussion To advance viral suppression, efforts should be made to ensure that all OVCLHIV are reached by community-based interventions as well as integrating food support in HIV treatment interventions.